1984
DOI: 10.1007/bf00383500
|View full text |Cite
|
Sign up to set email alerts
|

The expression of heat shock genes during normal development in Drosophila melanogaster (heat shock/abundant transcripts/developmental regulation)

Abstract: Drosophila melanogaster cells and tissues respond to heat shock by dramatically altering their pattern of transcription and translation, leading to the rapid synthesis of a small number of polypeptides, the heat shock proteins (hsps). By using cloned hsp DNA we have detected sequences complementary to heat shock genes in RNA prepared from non-heat-shocked animals of different developmental stages. Hsp 83 mRNA is present at high levels in all stages examined. Hsp 68 and 70 mRNAs are present at very low levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
0
6

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 39 publications
9
75
0
6
Order By: Relevance
“…mRNA for DmHsp22 has been reported to be expressed at different developmental stages and sequences required for expression of its gene during heat shock and normal development are partly defined (26,61). King and Tower (30) showed that DmHsp22 was one of the most abundant heat shock protein in aged flies.…”
Section: Dmhsp22: a Small Heat Shock Protein In D Melanogastermentioning
confidence: 99%
“…mRNA for DmHsp22 has been reported to be expressed at different developmental stages and sequences required for expression of its gene during heat shock and normal development are partly defined (26,61). King and Tower (30) showed that DmHsp22 was one of the most abundant heat shock protein in aged flies.…”
Section: Dmhsp22: a Small Heat Shock Protein In D Melanogastermentioning
confidence: 99%
“…The HSP70 gene itself is not activated under this condition but proteins for two HSPT0 family members are induced (35). An HSP70-1ike protein is one of the first proteins synthesized after zygote formation in mouse embryogenesis (4), and several HSPs are induced during oogenesis and pupation in Drosophila (25,36,44,59,70). …”
Section: Life Cycles and Heat Shock Proteinsmentioning
confidence: 99%
“…In animal systems, the greatest proportion of hsp synthesis is represented by the high molecular mass hsp of 68 to 110 kD, with polypeptides of 70 kD being the predominant species (see Ref. '21 for review). In Drosophila, it has been shown that several low mol wt hsp are synthesized in significant amounts during normal development (3,18). The functions of the hs proteins at control temperatures may not be the same as at the hs temperature (3).…”
mentioning
confidence: 99%